7s-4=26

Simple and best practice solution for 7s-4=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7s-4=26 equation:


Simplifying
7s + -4 = 26

Reorder the terms:
-4 + 7s = 26

Solving
-4 + 7s = 26

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 7s = 26 + 4

Combine like terms: -4 + 4 = 0
0 + 7s = 26 + 4
7s = 26 + 4

Combine like terms: 26 + 4 = 30
7s = 30

Divide each side by '7'.
s = 4.285714286

Simplifying
s = 4.285714286

See similar equations:

| x+0.833*x=7791.56 | | 2(3x-1)+3=21 | | 2x+40-6x=2-9x+3 | | 2x^2+54x=18 | | 3x-42=5x | | 8x+7x-54=180 | | 3x+3=12x-40 | | 2x^2+27x=9 | | x+0.833x=7791.56 | | x+0.833=7791.56 | | 5x-(2x-10)=25 | | 9v-8=6v-2 | | 30x-5=25 | | 10a-2=7a+11 | | c=45+0.5(72) | | (x+1)+(x+2)-5=6 | | y(y-5)=6 | | -9(x-4)=54 | | 6y+8=3(2y+3) | | 55*75-3= | | 141-4x=32x+21 | | 10x+2(-5x)=-6 | | 5-3(2x+4)=-6x+6 | | 3(x+4)=3x+11 | | 2800=.5s+1000 | | 2x+3=2x+7 | | 4(3-1)=2f+9 | | 20-p=3p | | 2(a-4)=2a+8 | | 4(a-6)=3(a+4) | | 2w+5=5w-25 | | 89-2x=10x-17 |

Equations solver categories